A Narrative Study of Counsellors’ Understandings of Inuit Spirituality - Wihak, Christine; Merali, Noorfarah (Canadian Journal of Counselling and Psychotherapy, 2007)
Eight non-Indigenous counsellors who temporarily lived in Nunavut to serve Inuit clients were interviewed regarding what they learned about Inuit spirituality during their cultural immersion experience. They were also asked about how they applied their understandings of the Inuit spiritual worldview in their professional practice. Counsellors’ narratives of their experiences in Nunavut revealed an understanding of the unity of humans and the natural environment in Inuit spirituality, alternate versions of reality, and diverse religious beliefs and rituals. Counsellors’ reflective practice facilitated a search for culturally meaningful explanations of clients’ presenting problems, as well as the use of culturally appropriate healing methods.